2022
DOI: 10.1001/jamaoto.2021.4105
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Sensorineural Hearing Loss During the COVID-19 Pandemic

Abstract: Sudden sensorineural hearing loss (SSNHL) is an emergency otologic condition with unknown pathophysiology that is mainly idiopathic. However, a viral cause was reported in temporal bone studies. 1 Several reports have suggested that there is an increased risk of SSNHL after COVID-19. 2 We aimed to compare the incidence of SSNHL during the COVID-19 pandemic with the incidence during 2018 and 2019 and to assess the association of lockdowns with incidence of SSNHL.Methods | Using data from the Clalit Health Servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 6 publications
3
19
0
1
Order By: Relevance
“…Van Rijssen et al tested 25 patients with SSNHL in a large Dutch teaching hospital for COVID-19 with no positive cases, and concluded no significant relationship between SSNHL and COVID-19 ( 23 ). Doweck et al used data from Clalit Health Services to compare the incidence of SSNHL during the COVID-19 pandemic in Israel with the incidence in 2018 and 2019, and found that the incidence of SSNHL decreased during the COVID-19 pandemic compared with the time before the COVID-19 outbreak ( 24 ). It might be related to the decrease in community physicians and emergency department visits ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Rijssen et al tested 25 patients with SSNHL in a large Dutch teaching hospital for COVID-19 with no positive cases, and concluded no significant relationship between SSNHL and COVID-19 ( 23 ). Doweck et al used data from Clalit Health Services to compare the incidence of SSNHL during the COVID-19 pandemic in Israel with the incidence in 2018 and 2019, and found that the incidence of SSNHL decreased during the COVID-19 pandemic compared with the time before the COVID-19 outbreak ( 24 ). It might be related to the decrease in community physicians and emergency department visits ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…Doweck et al used data from Clalit Health Services to compare the incidence of SSNHL during the COVID-19 pandemic in Israel with the incidence in 2018 and 2019, and found that the incidence of SSNHL decreased during the COVID-19 pandemic compared with the time before the COVID-19 outbreak ( 24 ). It might be related to the decrease in community physicians and emergency department visits ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…Very few studies have reported a decreased overall incidence of sudden SSNHL during the COVID-19 pandemic [ 34 , 35 ], possibly due to the widespread use of medical masks in association with social distancing. These aspects may have limited the spread of other viral infections and, possibly, also the onset of other SSNHL cases.…”
Section: Discussionmentioning
confidence: 99%
“…These aspects may have limited the spread of other viral infections and, possibly, also the onset of other SSNHL cases. Furthermore, it has been reported that, during the lockdown periods, patients may have delayed or avoided medical care, especially for non-life-threating conditions, and therefore SSNHL cases may have been underestimated [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…En los inicios de la pandemia por COVID-19 disminuyeron el número de urgencias en otorrinolaringología, al igual que el resto de las urgencias hospitalarias, entre ellas, el diagnóstico de nuevos casos de hipoacusia súbita. Las posibles causas fueron el confinamiento, el miedo de la población a contraer la infección en los centros hospitalarios, las restricciones en las visitas a los centros sanitarios [1][2][3] y la disminución en la incidencia de otras infecciones distintas al SARS-CoV-2 debido al uso de la mascarilla y el distanciamiento social [1]. Sin embargo, como podemos evidenciar en la literatura, son emergentes los casos de sordera súbita (SS), acúfeno y neuritis vestibular relacionados con la infección por el nuevo coronavirus [3], observándose un incremento notable de publicaciones acerca de las manifestaciones audiovestibulares del COVID-19 en forma de casos clínicos principalmente.…”
Section: Introductionunclassified